Pentingnya Berpikir Kritis dalam Pembelajaran Matematika - Rahmaini, Nurul; Ogylva Chandra, Salsabila (Griya Journal of Mathematics Education and Application, 2024)
Critical thinking is the ability to evaluate, analyze and organize information carefully and logically. This paper aims to describe critical thinking in mathematics. The method used in researching this article is literature study. The approach used is a literature study approach with sources coming from articles and journals. From several sources obtained, the most relevant data related to this article was taken. Based on several article sources, it can be seen that critical thinking is very impottant and is closely related to mathematics learning.